Weight of evidence analysis of the tumorigenic potential of 1, 3-dichloropropene supports a threshold-based risk assessment. (25th November 2020) - Yan, Zhongyu (June); Bartels, Michael; Gollapudi, Bhaskar; Driver, Jeffrey; Himmelstein, Matthew; Gehen, Sean; Juberg, Daland; van Wesenbeeck, Ian; Terry, Claire; Rasoulpour, Reza
Abstract: 1, 3-Dichloropropene (1, 3-D; CAS #542-75-6) is a fumigant used for preplant treatment of soil to control parasitic nematodes and manage soil borne diseases for numerous fruit, vegetable, field and tree and vine crops across diverse global agricultural areas. In the USA, 1, 3-D has historically been classified by the U.S. EPA as likely to be carcinogenic to humans via both oral and inhalation routes. This classification for the oral route was primarily based upon increases in multiple tumor types observed in National Toxicology Program (NTP) cancer bioassays in rats and mice, while the classification for the inhalation route was based upon increased benign bronchioloalveolar adenomas in a mouse study conducted by The Dow Chemical Company. Based on U.S. EPA standard risk assessment methodologies, a low-dose linear extrapolation approach has been used to estimate risks to humans. Furthermore, genotoxicity associated with 1, 3-D was historically considered a potential mode of action (MOA) for its tumorigenicity. New information is available and additional studies have been conducted that reveal a different picture of the tumorigenic potential of 1, 3-D. These data and information include: (1) initial cancer studies by the NTP were conducted on an antiquated form of 1, 3-D which contained a known mutagen/carcinogen, epichlorohydrin, as a stabilizer while current 1, 3-D fumigants use epoxidized soybean oil (ESO) as the stabilizer; (2) results from two additional oral rodent cancer bioassays conducted on the modern form of 1, 3-D became available and these two studies reveal a lack of carcinogenicity; (3) a newly conducted Big Blue study in F344 rats via the oral route further confirms that 1, 3-D is not an in vivo genotoxicant; and (4) a newly conducted repeat dose inhalation toxicokinetic (TK) study shows that linear dose proportionality is observed below 30 ppm, which demonstrates the non-relevance of 60 ppm 1, 3-D-induced benign lung tumors in mice for human health assessment. This weight of evidence review is organized as follows: (a) the TK of 1, 3-D are presented because of relevant considerations when evaluating test doses/concentrations and reported findings of tumorigenicity; (b) the genotoxicity profile of 1, 3-D is presented, including a contemporary study in order to put a possible genotoxicity MOA into perspective; (c) the six available bioassays are reviewed followed by (d) scientifically supported points of departure (PODs) and evaluation of human exposure for use in risk assessment. Through this assessment, all available data support the conclusion that 1, 3-D is not a tumorigen at doses below 12.5 mg/kg bw/day via the oral route or at doses below 30 ppm via the inhalation route. These findings and clearly identified PODs show that a linear low dose extrapolation approach is not appropriate and a threshold-based risk assessment for 1, 3-D is human health protective. Finally, in 2019, the Cancer Assessment Review Committee (CARC) reevaluated the carcinogenic potential of 1, 3-D. In accordance with the EPA's Final Guidelines for Carcinogen Risk Assessment, the CARC classified 1, 3-D (Telone) as "Suggestive Evidence of Carcinogenic Potential based on the presence of liver tumors by the oral route in male rats only." Given this finding, EPA stated that "quantification of human cancer risk is not required. The CARC recommends using a non-linear approach (i.e. reference dose (RfD)) that will adequately account for all chronic toxicity including carcinogenicity, that could result from exposure to 1, 3-dichloropropene."